Germination and early growth of Indian mustard (Brassica juncea L.) genotypes under saline conditions (Journal of Oilseed Brassica, 2026)
Salinity is a prominent abiotic stress in many parts of the world. It is the most important element that causes crop damage and lower yields. Mustard is one of the most salt-sensitive crops. An experiment was designed comprising fifteen genotypes of Indian mustard under varied saline levels (control, 8 dSm-1, 10 dSm-1, 12 dSm-1, and 14 dSm-1) to screen and identify resistant genotypes at the early seedling stage. Out of 15 genotypes, four genotypes (two tolerant genotypes viz., RH 725 and RH 1512 and, two susceptible genotypes viz., RH 1520 and RH 8812) were chosen for further studies at vegetative and flowering stages up to maturity, and grown in pots under greenhouse conditions with various salinity levels viz. control, 8 dSm-1, 10 dSm-1, and 12 dSm-1 compare the physiology and yield of these genotypes. As saline levels increased, negative impacts on germination percentage, seedling dry weight, seedling length, seedling vigor-I, seedling vigor-II, photosynthetic rate, transpiration rate, total biomass and 1000 seeds weight were detected. Lower salinity level (8 dSm-1) had no effect, whereas higher salinity levels resulted in a significant drop. The RH 1520 genotype showed the greatest reduction up to 50% under salinity levels, while the RH 725 genotypes demonstrated resilience ( 15%) to salinity levels.